Comparison of inflammatory markers in the differentiation of uncomplicated appendicitis and complicated appendicitis - NARSAT, Mehmet Ali; GÜLTEN, Sedat; YILDIZ, Eren; DURAK, Özlem; YILMAZ, Ayşe (MediHealth Academy, 2022)
Introduction: Appendicitis is the common emergency surgery performed in the pediatric age group. However, it has been reported in recent studies that some appendicitis cases will benefit from antibiotic treatment and that they can be followed up without surgery. In our study, it was aimed to compare the pre-operative inflammatory markers with the pathology results of the patients who were operated for appendicitis in our clinic and to reveal their success in the distinction between acute appendicitis and complicated appendicitis. Materials and Methods: The data of 98 patients who were operated with a pre-diagnosis of appendicitis in the pediatric surgery clinic of our hospital between 2019 and 2021 were retrospectively analyzed. Acute appendicitis and complicated appendicitis grouping was made according to pathological diagnoses. The inflammatory markers were evaluated. Results: According to the pathological grouping, 51 (56.7%) patients are in the acute appendicitis group. It was observed that only the change in the CRP value in the binary regression evaluation created for the parameters whose difference was significant evaluation increased the complicated appendicitis probability 1.028 times. It was seen that the CRP value of 34.65 was a parameter that could distinguish between acute appendicitis and complicated append with 79.5% sensitivity and 78.4% specificity. Conclusion: The treatment of appendicitis in children is a subject that is still being studied and has many points that have not been clarified. Among the markers that can be used in treatment planning, CRP gives usable results. More detailed and larger series are needed for other markers.
Keywords: 3. Good health